Diagnostic utility of flow cytometry in identifying histiocytic sarcoma—A case report. Issue 10 (22nd June 2022) - Kushwaha, Pritika; Singh, Meeta; Datwani, Sneha; Mallya, Varuna; Singh, Sarika; Aggarwal, Sunita
Abstract: Histiocytic sarcoma (HS) is a malignant neoplasm of hematopoietic origin. It is an exceedingly rare and aggressive malignancy commonly seen in adults. Diagnosis is difficult owing to lack of specific clinical manifestations with the absence of precursor lesions or causative agents. Hence, it primarily relies on histopathological morphology combined with immunohistochemistry, which is time‐consuming, hence resulting in delayed treatment. However, diagnostic utility of flow cytometry is not well established in this. We report a case of a 45‐year‐old man who presented with right axillary lymphadenopathy for 1 month. FNAC was performed on the axillary lymph node, which showed large, atypical lymphoid/histiocyte‐like cells. On flow cytometry, these cells were CD64+, CD11c+, and CD45+ suggesting histiocytic sarcoma. Similar morphology was seen on incisional biopsy. On immunohistochemistry, the cells were negative for B and T cell markers, PAX5, EMA, CK, ALK, and CD1a and expressed CD68, S100, and CD11c. A diagnosis of histiocytic sarcoma was made. Hence, flow cytometry can be a highly effective and powerful tool for the early detection of HS and can help in prompt treatment, given its aggressive clinical course and low survival interval.